DIDACTIC MATERIAL AIDS IN EDUCATION OF INFORMATICS - MALIŠ, Petr (Trends in education, 2019)
The paper brings the theoretical basis and categorization of educational material for the planned research. The theoretical summary of the term didactics aids is followed by further division of material aids. The first chapter deals with didactic material aids in the context of education of informatics. The usage of computers as an intermediary of content was chosen as the main characteristic of education. There is also stated a categorization of educational materials for the education of informatics. They are divided into four groups: electronic aids, printed educational materials, digital learning objects, and other tools. As the key group was chosen digital learning materials, which are described further in the second chapter. Digital learning objects consist of a huge variety of materials, into which belongs, for example, static documents and interactive animations. In this context, there are stated two important attributes - multimediality and interactivity. In the last chapter, there is presented the upcoming research from the field of didactics material aids. This research will be focused on the teachers of primary schools. The main topics will be the usage of different kinds of educational materials, attitudes of teachers towards their own creation of educational materials and selection preferences when choosing didactic aids.
Keywords: Didactics aids; education of informatics; educational materials